Separation of Nickellrom Plating Solution by Sulluration TreatmentT - T. Fukuta; T. Ito; K. Sawada; Yoshihiro Kojima; Eileen C. Bernardo; Hitoki Matsuda; K. Yagishita (Department of Chemical Engineering, Universitas Gadjah Mada, 2004)
Precipitation by sulfuration of nickel was used to recover nickel from the waste plating solution. Three kinds of sulfurating agents-sodium sulfide (Na2S), sodium disulfide (Na2S2),and sodium tetrasulfide (Na2S4)-were compared for the sulfuration behavior and the precipitation characteristics of the nickel sulfide (NiS) produced. Results showed that the nickel concentration in the filtrate was reduced from the initial concentration of 100 mRN/L to about 0.594-3.37 mRN/L with the addition of each sulfurating agent. The average specific filtration resistance of the slurry produced by adding each sulfurating agent was smaller than that in the nickel hydroxide (NiOH) slurry. In particular, the average specific filtration resistance of the slurry produced by adding Na2S4 was greatly reduced under controlled pH values of 7:t 1. The good filtration property obtained from the proposed sulfuration treatment was attributed to the larger particle-size distribution of NiS produced by the sulfuration agent Na2S4. It was further confirmed that the proposed sulfuration treatment using Na2S was applicable for the separation of nickel, zinc, and copper in mixed-metal solutions.